2015
DOI: 10.1016/j.prnil.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumor-associated macrophages and microvessel density on prostate cancer progression

Abstract: BackgroundTo evaluate tumor-associated macrophages (TAMs) infiltration and microvessel density as possible prognostic factors related to prostate cancer (PCa) progression.MethodsImmunostaining of TAMs in prostate biopsy specimens was performed using a monoclonal antibody CD68 and microvessel density (MVD) using von Willebrand factor (vWF) from 25 specimens with high-grade prostatic intraepithelial neoplasia (HGPIN) and 25 specimens with PCa after transurethral resection of the prostate (TURP). Six microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…In addition, various studies have shown that angiogenesis is crucial for the prognosis, metastasis, and progression of cancer. 4,27 We found that the MVD was significantly higher in the LETM1-positive group than in the negative group. We speculate that LETM1 plays an important role in tumor initiation and cancer progression and indicates poor PCa prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, various studies have shown that angiogenesis is crucial for the prognosis, metastasis, and progression of cancer. 4,27 We found that the MVD was significantly higher in the LETM1-positive group than in the negative group. We speculate that LETM1 plays an important role in tumor initiation and cancer progression and indicates poor PCa prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…The most common method for semiquantitative evaluation of neoangiogenesis is microvessel density (MVD) using endothelial markers such as CD31, CD34, CD105, and von Willebrand factor (vWF; refs. 16,17). Using a CD31 antibody and found an increased MVD in AA compared with EA patients ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Em outros estudos a infiltração de TAM não mostrou piora no prognóstico para o câncer de cólon e de mama (ZHOU et al, 2010;MAHMOUD et al, 2012). No câncer de próstata em humanos, o aumento de TAM não foi relacionado como um valor prognóstico independente (YURI et al, 2015). Os TAM são fontes de MMP-9 em cânceres de mama, de vesícula urinária e nos carcinomas ovarianos em humanos, tumores nos quais a expressão de MMP foi mais elevada do que nos tecidos normais (GOLLAPUDI et al, 2013).…”
Section: -Macrófagosunclassified
“…O microambiente tumoral vem sendo bastante estudado nos últimos anos e há evidências que células vasculares, fibroblastos e leucócitos desempenham papéis importantes na progressão do tumor e da metástase, sendo cada vez mais evidenciado que os TAMs representem os leucócitos infiltrantes que mais tem relação a um pior prognóstico (YUAN, et al, 2014). A presença de TAM em diferentes tipos de câncer em humanos e sua habilidade em promover angiogênese e facilitar desenvolvimento de metástases tem sido amplamente estudada (LEEK et al, 1996;BINGLE et al, 2006;MANTOVANI et al, 2010;YURI et al, 2015). (KÜBLER et al, 2012;YUAN et al, 2014).…”
unclassified
See 1 more Smart Citation